1993
DOI: 10.1177/089686089301302s19
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an Experimental Infection Model for Peritoneal Dialysis: Effect of Inoculum and Volume

Abstract: The effect of the number of bacteria and the volume of the inoculum was studied in an experimental infection model to establish a peritoneal dialysis model in the rat. Staphylococcus aureus was used in all experiments, and Staphylococcus epidermidis only in the volume experiments. A bacterial number between 108 and 109 colony forming units (cfu) resulted in a time-dependent decrease of bacteria collected from the peritoneal cavity. Higher concentrations resulted in the death of animals, while lower concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…An experimental infection model in the rat was established in which the effect of inoculum and volume on bacterial killing was investigated [66]. A suspension of 0.5 ml, containing 3 ϫ 10 8 Staphylococcus aureus (ATCC 25923) was injected into the peritoneal cavity of the rat.…”
Section: A Rat Model For the Study Of Peritoneal Defense Mechanismsmentioning
confidence: 99%
“…An experimental infection model in the rat was established in which the effect of inoculum and volume on bacterial killing was investigated [66]. A suspension of 0.5 ml, containing 3 ϫ 10 8 Staphylococcus aureus (ATCC 25923) was injected into the peritoneal cavity of the rat.…”
Section: A Rat Model For the Study Of Peritoneal Defense Mechanismsmentioning
confidence: 99%
“…The quantitative analysis done in Study 2 confirmed the initial observation. All three dosages of CFU cause a non-lethal peritonitis in rats, from which they recover spontaneously (20). The changes in serum α2M and albumin were most pronounced in group 3, which received the highest inoculum, but were also present in the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…[85] In the present study, a S. aureus inoculum of 2 × 10 8 CFU mL −1 (0.5 mL) was used to develop peritoneal infection based on the inoculum used in previous rat studies. [11,86] We used two rats, one as an uninfected control, and the other rat inoculated with S. aureus during surgical catheter placement to develop peritonitis. [11] The catheter with the sensor was placed in the peritoneal cavity, with the sensor in contact with the peritoneal fluid (Figure 3a,b).…”
Section: Animal Studymentioning
confidence: 99%